Health Benefits of the most Popular Alternative Sweetener, Stevia rebaudiana (Asian Journal of Pharmaceutics (AJP), 2026)
Known for its natural sweetening properties, Stevia rebaudiana is among the most popular species belonging to the Asteraceae family. The genus Stevia comprises 154 species, including the Paraguayan sweet plant. Various glycosides found in the shrub’s leaves impart it a sweet taste but have no caloric value. However, only S. rebaudiana has the ultimate level of sweetness among these species. Stevia extracts are high in steviol glycosides, which are sweetening agents that have antifungal, antibacterial, and antioxidant properties. This review’s primary goal is to provide a current summary of stevia’s antibacterial, antioxidant, and antidiabetic properties as well as its immune-boosting properties. In addition to its health benefits, stevia has been used in industry, specifically as food and food ingredients; as a substitute for sucrose; as animal feed and fertilizer; and as a solubilizing or foaming agent